Pengaruh Budaya Berorientasi Hasil terhadap Kinerja Organisasi Sektor Publik dengan Akuntabilitas Keuangan sebagai Variabel Intervening - Sariyanah, Sariyanah; Dwita, Sany (Wahana Riset Akuntansi, 2024)
Purpose – This research aims to empirically test the mediating role of financial accountability in the relationship between results-oriented culture and the performance of public sector organizations in Tanjung Jabung Timur Regency.Methodology – This research uses quantitative methods with survey techniques. The survey sample of 130 respondents came from employees who work in the Regional Apparatus Organization (OPD) of Tanjung Jabung Timur Regency. The sampling technique uses purposive sampling. Data analysis in the form of CMB test, descriptive statisticsFindings – The research results show that a results-oriented culture has a positive impact on organizational performance, and financial accountability plays a mediating role in the relationship between a results-oriented culture and the performance of public sector organizations in the OPD of Tanjung Jabung Timur Regency.Originality/value – This research was first carried out in Indonesia within the scope of public sector organizations in developing countries and made several contributions. First, filling the gap in the literature by providing empirical evidence about the influence of a results-oriented culture on the performance of public sector organizations through financial accountability, especially in Indonesia. Second, it supports NPM theory in confirming the positive influence of a results-oriented culture on financial accountability and performance of public sector organizations.Limitations/implications – The scope of the research is still limited, so the research results cannot be generalized. In addition, collecting data using surveys allows for honesty factors from respondents which can influence data quality. Future research could expand the research sample and add interview methods. This research provides practical implications for public sector organizations, especially for the Tanjabtim Regency OPD who want to improve their performance through implementing a results-oriented culture and effective financial accountability.